Genomic basis of recombination suppression in the hybrid between Caenorhabditis briggsae and C. nigoni. Issue 3 (9th January 2018) - Ren, Xiaoliang; Li, Runsheng; Wei, Xiaolin; Bi, Yu; Ho, Vincy Wing Sze; Ding, Qiutao; Xu, Zhichao; Zhang, Zhihong; Hsieh, Chia-Ling; Young, Amanda; Zeng, Jianyang; Liu, Xiao; et al.
Abstract: DNA recombination is required for effective segregation and diversification of genomes and for the successful completion of meiosis. Recent studies in various species hybrids have demonstrated a genetic link between DNA recombination and speciation. Consistent with this, we observed a striking suppression of recombination in the hybrids between two nematodes, the hermaphroditic Caenorhabditis briggsae and the gonochoristic C. nigoni . To unravel the molecular basis underlying the recombination suppression in their hybrids, we generated a C. nigoni genome with chromosome-level contiguity and produced an improved C. briggsae genome with resolved gaps up to 2.8 Mb. The genome alignment reveals not only high sequence divergences but also pervasive intra- and inter-chromosomal sequence re-arrangements between the two species, which are plausible culprits for the observed suppression. Comparison of recombination boundary sequences suggests that recombination in the hybrid requires extensive sequence homology, which is rarely seen between the two genomes. The new genomes and genomic libraries form invaluable resources for studying genome evolution, hybrid incompatibilities and sex evolution for this pair of model species.